Pelatihan tes Uji Kemahiran Berbahasa Indonesia (UKBI) di SMK Al–Husna Bojong Gede - Vickry Ramdhan; Randi Ramliyana; Usman Sutisna (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
Language skills are needed at all times in every segment of social life. The level of sound and correct Indonesian language skills differs for each individual. Testing a person's ability to speak Indonesian both verbally and in writing can be done by undergoing the "Indonesian Language Competency Test." With this, one can know the level of Indonesian language proficiency and can adjust to the expected language needs. Indonesian Language Proficiency Test is a means to measure a person's proficiency in spoken and written Indonesian. UKBI consists of five sections, namely Section I (Listening), Section II (Responding to Rules), Section III (Reading) in the form of multiple choice, Section IV (Writing) in the form of written presentations, and Section V (Speaking) in the form of presentations. Oral. During the current Covid-19 pandemic, UKBI cannot be held offline and in bulk in one place. UKBI Adaptive is a test to measure Indonesian speakers' language proficiency, which is a new thing for students at SMK AL-Husna Bojong Gede, so it needs to be socialized and tested. This study aimed to determine the Indonesian language's mastery for teachers at SMK Al-Husna Bojong Gede. Descriptive and quantitative methods were used in the study. The results showed that most of the participants scored between 300-400, which means that their abilities were in the pretty good category. Thus, it can be said that the UKBI is a test tool that can be used to measure the mastery of the Indonesian language and the teacher's good and correct use of Indonesian